Emergency department diagnosis of acute abdominal pain in elderly patients - Rittirak Othong; Prasit Wuthisuthimethawee; Prasert Vasinanukorn (Journal of Health Science and Medical Research (JHSMR), 2010)
Objective: To study the incidence and correctness of diagnoses in elderly patients examined in the Emergency Department (ED) for acute abdominal pain and compare the morbidity and mortality of patients whom are diagnosed in agreement and disagreement between the final and initial diagnoses. Material and Methods: This was a retrospective study of 378 elderly patients examined in the ED for acute non-traumatic abdominal pain from January 1 through December 31, 2005. The patients’ medical records were reviewed for demographics, initial diagnosis, final diagnosis, length and cost of hospitalization, mortality and morbidity. Results: Of 378 patients; median age 71 (60- 94 years; 46.3% were men and 71.2% had underlying diseases. 83.1% were diagnosed correctly and the common causes were nonspecify 35.2%; acute gastritis, gastroenteritis and diarrhea 10.6%; cholecystitis, cholelithiasis and biliary tract disease 8.2%. 26.5% of all patients were admitted, and in this subgroup, the diagnoses were correct only 66% of the time and the common diagnoses were cholecystitis, cholelithiasis and biliary tract disease 30.0%; intestinal obstruction 17.0%; nonspecify 10.0%. The patients who had discordance between initial and final diagnoses increased morbidity significantly since they had more hospitalization time (5.5 VS 8.0 days) and costs (12,107 VS 22,674 Baht), (p = 0.016 and 0.022, respectively). Fortunately, no one died in our study. Conclusion: This study examined the rate of incorrect diagnoses in elderly patients admitted to our ED due to acute abdominal pain. The impacts of incorrect diagnoses are mainly prolonged hospitalization and increased hospital costs.